Contributions of Natural and Anthropogenic Forcing Agents to the Early 20th Century Warming - Egorova, Tatiana; Rozanov, Eugene; Arsenovic, Pavle; Peter, Thomas; Schmutz, Werner (Frontiers in Earth Science, 2018)
The warming observed in the early 20th century (1910–1940) is one of the most intriguing and less understood climate anomalies of the 20th century. To investigate the contributions of natural and anthropogenic factors to changes in the surface temperature, we performed seven model experiments using the chemistry-climate model with interactive ocean SOCOL3-MPIOM. Contributions of energetic particle precipitation, heavily (shortwave UV) and weakly (longwave UV, visible, and infrared) absorbed solar irradiances, well-mixed greenhouse gases (WMGHGs), tropospheric ozone precursors, and volcanic eruptions were considered separately. Model results suggest only about 0.3 K of global and annual mean warming during the considered 1910–1940 period, which is smaller than the trend obtained from observations by about 25%. We found that half of the simulated global warming is caused by the increase of WMGHGs (CO2, CH4, and N2O), while the increase of the weakly absorbed solar irradiance is responsible for approximately one third of the total warming. Because the behavior of WMGHGs is well constrained, only higher solar forcing or the inclusion of new forcing mechanisms can help to reach better agreement with observations. The other forcing agents considered (heavily absorbed UV, energetic particles, volcanic eruptions, and tropospheric ozone precursors) contribute less than 20% to the annual and global mean warming; however, they can be important on regional/seasonal scales.